POVERTY IN THE RICH NATURAL RESOURCES AREA - Novianto, Efri (Jurnal Penelitian Kesejahteraan Sosial, 2020)
Samboja Sub District is an area that has a wealth of natural resources in the form of oil and gas. With abundant natural resources, Samboja residents can be more prosperous and free from poverty, but the reality is just the opposite. The purpose of this study was to determine the causes of poverty and its coping strategies. The approach used was descriptive qualitative with in-depth interview data collection techniques and literature study. While the analysis tool used is interactive data analysis. Based on the results of the study it was found that in general the majority of causes of poverty in Samboja District were related to social, cultural and structural factors. Socially, poverty is caused by the socio-economic conditions of poor families due to not having a job (unemployment), so they do not have a definite income to support household life. Culturally, poverty in Samboja Subdistrict was caused by cultural factors of the local community related to sanitation, especially the poor in the coastal areas (coast). While structurally, poverty in Samboja Subdistrict was caused by discrimination against poverty alleviation policies for certain poor families and minimal budget allocation. The poverty reduction strategy that should be carried out by the government of Kutai Kartanegara Regency in the short term is to directly intervene poor households by tackling several poverty indicators, while in the long run it is directed at activities empowering in accordance with the potential families of poor.